Cardiovascular risk factors and cardiovascular disease in patients with type 1 diabetes and end-stage renal disease candidates for kidney-pancreas transplantation: Trends from 1999 to 2017. (May 2020) - Ruiz, Sabina; Amor, Antonio Jesús; Pané, Adriana; Molina-Andujar, Alicia; Montagud-Marrahi, Enrique; Ventura-Aguiar, Pedro; Ferrer-Fàbrega, Joana; Esmatjes, Enric
Abstract: Aims: To evaluate the changes in cardiovascular risk factors (CVRFs) and cardiovascular disease (CVD) in patients with type 1 diabetes (T1D) and end-stage renal disease (ESRD) who were candidates for kidney-pancreas transplantation (KPTx) from 1999 to 2017. Methods: Patients with T1D referred for KPTx evaluation were included. The cohort was divided into five groups according to the year of evaluation (1999–2002, 2003–2006, 2007–2010, 2011–2014 and 2015–2017). The control of CVRFs and the prevalence of prior CVD were evaluated. Results: We evaluated 360 patients (64.4% men, age 38.9 ± 7.1 years). LDL-cholesterol <100 mg/dl increased from 22.7% to 76.9% (1999–2002 vs. 2015–2017; p < 0.001), as did the use of statins (from 24.7% to 74.5%; p < 0.001). Systolic blood pressure decreased from 138.8 ± 27.6 to 125.1 ± 27.9 mmHg (p = 0.001) and current smokers from 48% to 25% (p = 0.018). Intensive insulin treatment increased from 34.4% to 93.6% (p < 0.001). Diabetes duration before the initiation of renal replacement therapy increased from 23 ± 5.5 to 26.9 ± 8.9 years (p = 0.001). Overall, 30.3% had previous CVD, without significant changes over time (p = 0.699), albeit patients were older and had longer diabetes duration. Conclusions: Patients with T1D and ESRD referred for KPTx have better control of CVRFs over time, which might lead to a decrease in cardiovascular events.